1986
DOI: 10.1037/0021-843x.95.4.395
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of parent–child relationships in eating disorders.

Abstract: This study tested the psychodynamic formulation that binge eating in bulimia reflects familial and intrapsychic deficits in nurturance, empathy, and to some extent, affective regulation. The study compared parental relationships and introjects among young women (N = 80) with bulimia, bulimia-anorexia, anorexia, and normal controls using Benjamin's Structural Analysis of Social Behavior model and rating scales. As expected, the results revealed that the two bulimic subgroups experienced deficits in parental nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
2
3

Year Published

1987
1987
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 20 publications
5
80
2
3
Order By: Relevance
“…While many perspectives on anorexia currently emphasize either biological (Hendren, 1983;Swift, Andrews, & Barklage, 1986) or sociocultural (Bemporad, Ratey, O'Driscoll, & Daehler, 1988;Orbach, 1986;Steiner-Adair, 1986) correlates, the young women in this study, as in others (Humphrey, 1986;Strober & Humphrey, 1987;Beattie, 1988;Armstrong & Roth, 1989;Stern, 1991), illustrate the relationship between maternal attachment patterns and subsequent development of eating disorders.…”
Section: Ambivalent Attachment and Eating Disordersmentioning
confidence: 82%
“…While many perspectives on anorexia currently emphasize either biological (Hendren, 1983;Swift, Andrews, & Barklage, 1986) or sociocultural (Bemporad, Ratey, O'Driscoll, & Daehler, 1988;Orbach, 1986;Steiner-Adair, 1986) correlates, the young women in this study, as in others (Humphrey, 1986;Strober & Humphrey, 1987;Beattie, 1988;Armstrong & Roth, 1989;Stern, 1991), illustrate the relationship between maternal attachment patterns and subsequent development of eating disorders.…”
Section: Ambivalent Attachment and Eating Disordersmentioning
confidence: 82%
“…Strober, Salkin, Burroughs, and Morrell (1982) also compared the Minnesota Multiphasic Personality Inventory (MMPI) profiles from 35 parents of bulimic anorexics with those of 35 parents of restricting anorexics and found the parents of the bulimic subgroup to be significantly more hostile, impulsive, and excitable than the parents of the restricting subgroup. Humphrey (1986cHumphrey ( , 1986d) has compared these three subtypes of eating disorders with one another and with normal control subjects and has found that, whereas all three clinical groups perceived their relationships as more blaming, rejecting, and neglectful relative to control subjects, only the two bulimic subgroups also perceived a deficit in parental nurturance and empathy (Humphrey, 1986e). Compared with the families of restricting anorexics, the families of bulimics were more hostilely enmeshed and deficient in affection and support, whereas the families of restricting anorexics more frequently juxtaposed opposing messages of affection and caring with enmeshment and negation of the child's needs.…”
Section: Familial Influences On Illness Course and Clinical Heterogenmentioning
confidence: 99%
“…The question of whether the fathers are remote is therefore unclear if they are also reported as being overinvolved. Humphrey's (1986) findings suggest that the relationship with the father may be more important etiologically than is traditionally claimed in analytic theory. The impact of the fathers upon the development of eating disorders has not been examined as extensively as that of the mothers.…”
Section: Family Influencementioning
confidence: 47%
“…Humphrey (1986) examined the deficits in nurturance, empathy, and affective regulation on both a familial and intraphysic level as possible contributors to eating disorders using Benjamin's Structural Analysis of Social…”
Section: Family Influencementioning
confidence: 99%